Investigation of residual stresses in Q460GJ steel plates from medium-walled box sections. (September 2018) - Nie, Shidong; Zhu, Qian; Yang, Bo; Li, Pengcheng
Abstract: Residual stress is an important factor that can have considerable effect on the behaviour of steel structures. In the past, most of the research has been focused on determining the residual stress in members consisting of traditional normal strength and high strength steels. There has been little research on residual stresses in members fabricated from high performance steels such as GJ steel. The work detailed in this paper aims to experimentally investigate the residual stresses in welded box sections fabricated from Q460GJ high performance structural steel plates. A total of eight full-scale welded box sections, with nominal wall thicknesses of 12 mm and 25 mm, were tested using the sectioning method. Both the circular curve correction method and the straightening measurement method were used in this study to obtain the magnitude and distribution of the longitudinal residual stresses. In addition, the effects of steel plate thickness and the plate width-to-thickness ratio on the residual stress were investigated. A simplified residual stress distribution model, which would be of great assistance in investigating the buckling behaviour of GJ-type steel members, is proposed based on the experimental results. Highlights: The residual stresses of medium-walled box sections fabricated from Q460 GJ steel plates were tested. The residual stresses in the inner sides and outer sides of welded medium-walled box sections were demonstrated. A simplified residual stress model for medium-walled box sections fabricated from Q460 GJ steel plates was proposed.